Iron overload as a risk factor for hepatic ischemia‐reperfusion injury in liver transplantation: Potential role of ferroptosis. Issue 6 (3rd February 2020) - Yamada, Naoya; Karasawa, Tadayoshi; Wakiya, Taiichi; Sadatomo, Ai; Ito, Homare; Kamata, Ryo; Watanabe, Sachiko; Komada, Takanori; Kimura, Hiroaki; Sanada, Yukihiro; Sakuma, Yasunaru; Mizuta, Koichi; et al.
Abstract : Hepatic ischemia‐reperfusion (I/R) injury is a major problem in liver transplantation (LT). Although hepatocyte cell death is the initial event in hepatic I/R injury, the underlying mechanism remains unclear. In the present study, we retrospectively analyzed the clinical data of 202 pediatric living donor LT and found that a high serum ferritin level, a marker of iron overload, of the donor is an independent risk factor for liver damage after LT. Since ferroptosis has been recently discovered as an iron‐dependent cell death that is triggered by a loss of cellular redox homeostasis, we investigated the role of ferroptosis in a murine model of hepatic I/R injury, and found that liver damage, lipid peroxidation, and upregulation of the ferroptosis marker Ptgs2 were induced by I/R, and all of these manifestations were markedly prevented by the ferroptosis‐specific inhibitor ferrostatin‐1 (Fer‐1) or α‐tocopherol. Fer‐1 also inhibited hepatic I/R‐induced inflammatory responses. Furthermore, hepatic I/R injury was attenuated by iron chelation by deferoxamine and exacerbated by iron overload with a high iron diet. These findings demonstrate that iron overload is a novel risk factor for hepatic I/R injury in LT, and ferroptosis contributes to the pathogenesis of hepatic I/R injury. Abstract : This study demonstrates that iron overload is a novel risk factor for hepatic ischemia‐reperfusion injury in liver transplantation, and ferroptosis contributes to the pathogenesis of hepatic ischemia‐reperfusion injury.